What Do You Know about Alternative Energy? Development and Use of a Diagnostic Instrument for Upper Secondary School Science - Cheong, I.; Johari, M.; Said, H.; Treagust, David (Routledge, 2015)
The need for renewable and non-fossil fuels is now recognised by nations throughout the world. Consequently, an understanding of alternative energy is needed both in schools and in everyday life-long learning situations. This study developed a two-tier instrument to diagnose students’ understanding and alternative conceptions about alternative energy in terms of: sources of alternative energy, greenhouse gas emission, as well as advantages, and disadvantages. Results obtained with Years 10 and 11 students (n = 491) using the 12-item two-tier instrument (α = 0.61) showed that students’ understanding of alternative energy was low (M = 7.03; SD = 3.90).The 23 alternative conceptions about alternative energy sources that could be identified from the instrument are reported. The implications for teaching and learning about alternative energy and suggestions for further development and improvement of the instrument are presented.